Disfunción familiar y su incidencia en las relaciones interpersonales - Bustamante Jordan, Andres Enrique (2020)
This case study has as its theme: family dysfunction and its impact on interpersonal relationships and as an objective it was established to analyze the incidence of family dysfunction in interpersonal relationships of a 14-year-old adolescent with intellectual disability, in Naranjito canton, province from Guayas. In order to make the diagnosis, several instruments of psychodiagnostic assessment, clinical history, observation guide, the Test in the rain and the family genogram were used. Their analysis confirmed the presence of a dysfunctional family with a diverter-attacker Triana. One of the most affected areas of the patient was the affective area, so the therapeutic strategies employed were family systemic techniques, developing a therapeutic scheme that was formed by: objective, affectivity, technique, dates, number of sessions and the expected results, this technique was aimed at the recovery of the patient in the aspect of affectivity. Once the treatment was completed, the goals set were partially met, despite this there were significant improvements in the patient’s emotional and family environment, reducing conflicts between family members and giving each one the right to Be heard respecting your decision in any situation.